The Influence of Electronic Word of Mouth on Somethinc Brand Image Among Millienial and Gen Z - Madyna Zalza Azahra Suhajar; Dini Salmiyah Fithrah Ali; Amanda Bunga Gracia (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The large number of people using Twitter to obtain information has resulted in several Twitter accounts using the autobase feature, such as the @ohmybautybank account. On the @ohmybautybank account, there are many discussions about cosmetic and skincare products. This study aims to measure how much influence Electronic Word of Mouth has on Brand Image Somewhat among Millennials and Gen Z (Study of Followers of the Ohmybautybank Twitter Account). The research method used was quantitative descriptive, using a probability sampling technique to 400 respondents was carried out by distributing questionnaires online to followers of the Twitter account @ohmybeautybank. Based on the results of the analysis of the Electronic Word of Mouth regression model on social media Twitter has a significant influence on Brand Image Something. Then the influence of Electronic Word of Mouth on Brand Image Something is 42.2% while the rest is influenced by other factors outside this study.